2001
DOI: 10.1038/sj.bmt.1702779
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytic activity against Streptococcus pneumoniae type 19F in allogeneic BMT recipients before and after vaccination with pneumococcal polysaccharide vaccine

Abstract: Summary:Opsonophagocytic activity (OPA) of pneumococcal polysaccharide (Pnc PS) antibodies in vitro, a measure of antibody functional activity, usually correlates with specific IgG antibody concentrations measured by an EIA method. In order to investigate the functional activity of specific Pnc PS antibodies, we determined IgG antibodies to Pnc PS type 19F by an EIA method and OPA against Pnc type 19F by a killing assay in a randomized study, where 23 adult allogeneic BMT recipients were vaccinated with Pnc PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Antibodies to Spn capsular polysaccharides [43,44] and to pneumococcal surface protein A (PspA) [42] mediate opsonophagocytic killing of Spn. This study and our previous study [29] have shown that vaccination with trivalent PPrV elicits high sera and lung mucosal IgG responses to PhtD, PcpA and PlyD1 in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to Spn capsular polysaccharides [43,44] and to pneumococcal surface protein A (PspA) [42] mediate opsonophagocytic killing of Spn. This study and our previous study [29] have shown that vaccination with trivalent PPrV elicits high sera and lung mucosal IgG responses to PhtD, PcpA and PlyD1 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-mediated opsonization and phagocytosis is an important defense mechanism against Spn [42][43][44]. Antibodies to Spn capsular polysaccharides [43,44] and to pneumococcal surface protein A (PspA) [42] mediate opsonophagocytic killing of Spn.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and mouse protection data for the selected serotypes for which this assay works indicate that the opsonophagocytosis assay provides the best basis for protection (12,24). Measuring OPA titers has revealed low functional activity of conjugate vaccine-induced antibodies in bone marrow transplant recipients (18) and different responses to conjugate and plain polysaccharide vaccines in children and adults with sickle cell disease (25).…”
mentioning
confidence: 99%
“…However, the ELISA assay does not always predict serotype protection, especially in older adults and immunosuppressed populations [24,25]. This may be due to lack of IgM support [24] or production of polyreactive, but nonspecific, IgG antibodies [25]. As a result, a functional assay that measures the capacity of detected antibody to opsonize and kill pneumococcus has emerged as a potentially more specific surrogate marker.…”
Section: Surrogate Markers Of Immunogenicitymentioning
confidence: 98%
“…Serologic measurement of IgG against the pneumococcal antigen using ELISA assays was the first surrogate used, with antibody levels greater than 0.2-0.35 mg/l thought to offer protection against vaccine-targeted serotypes [23]. However, the ELISA assay does not always predict serotype protection, especially in older adults and immunosuppressed populations [24,25]. This may be due to lack of IgM support [24] or production of polyreactive, but nonspecific, IgG antibodies [25].…”
Section: Surrogate Markers Of Immunogenicitymentioning
confidence: 99%